ANALISIS PEMANFAATAN APLIKASI BRISPOT PADA UMKM DI YOGYAKARTA - Tyagita Dianingtyas Sudibyo (Universitas Mercu Buana Yogyakarta, 2021)
MSME contributes Indonesia's national economy, as well as being one of the proponents of economic growth in Indonesia. However, there are fundamental problems in MSME that have occurred for a long time, which is the difficulty in handling large demands from consumers and lack of capital. BRI is a bank that focuses on handling micro-businesses. There are several obstacles when submitting a KUR, namely the time requirement, fraud, paper base, particular space requirement for storing application files. BRI is a pioneer in the creation and the use of a credit application called BRISPOT. This research uses descriptive method with qualitative approach, which is a research with a process and understanding based on the methodology of investigating social phenomena and problems that occur to humans. The sample used is BRI KUR mantri which has a rating of 1-5 in terms of achieving the target for the last 6 months and their customers are MSME subjects.Data collection uses interview techniques which are conducted by telephone and visiting the subject directly. The data are processed using selective coding techniques. The conclusion of this study is the BRISPOT application has a significant effect on the speed of submitting KUR for MSME. Start from faster in time to higher level of data accuracy. The BRISPOT application can also suppress fraud committed by both customers and mantri.